KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK TERKOMPLIKASI YANG MENJALANI HEMODIALISA DI RS “X” KOTA SEMARANG - FX Sulistiyanto Wibowo S; Erna Prasetyaningrum (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
Quality of life is a condition where a person gets satisfaction or enjoyment in everyday life. The quality of life concerns physical health and mental health, which means that if a person is physically and mentally healthy, that person will achieve satisfaction in his life. Physical health can be assessed from physical function, physical role limitations, body pain, and perceptions of health. Mental health itself can be assessed from social function and the limitations of the emotional role. In addition, indicators of quality of life include the domain of physical health, the domain of psychological well-being, the domain of social relations, and the domain of relationships and the environment. Chronic kidney failure is in the top 20 causes of death in the world and the top 10 causes of death in Indonesia. Problems that arise due to chronic kidney failure are multi-organ disorders, accumulation of urea, which can cause poisoning, edema, anemia, and a drastic decrease in physical abilities, reducing the patient's quality of life.This research is a type of research conducted as an exploratory descriptive study with a cross-sectional design. This research was carried out at the "X" Hospital in Semarang City from October 1, 2021 to December 31, 2021. The number of chronic kidney disease patients undergoing hemodialysis at the hospital was 50 people. Age of adult patients, data collection techniques in this study using a sampling technique that is random sampling. The tool used in this study was a questionnaire adopted by BREF on the World Health Organization's quality of life (WHOQoL) consisting of 26 questions covering four areas, namely physical, psychological, environmental, and social needs to be achieved. insight into the quality of life of chronic kidney disease patients undergoing dialysis. As a data collection tool in this study, validity and reliability tests were carried out.The quality of life of kidney failure patients undergoing hemodialysis at the Semarang City Hospital "X" showed poor, as many as 27 respondents (54%). The physical domain of the quality of life of kidney failure patients undergoing hemodialysis showed poor results, as many as 29 respondents (58%). The quality of life in terms of the psychological domain of kidney failure patients undergoing hemodialysis showed poor results, as many as 32 respondents (64%). The environmental domain of the quality of life of kidney failure patients undergoing hemodialysis showed good results, namely as many as 29 respondents (58%) and the domain of social relations, the quality of life of kidney failure patients undergoing hemodialysis showed good results, as many as 33 respondents (66%).  Keywords: Chronic Kidney Failure, Complications, Haemodialysis, Quality of Life, WHOQoL-BREF.